More Than (Single) Text Comprehension? – On University Students’ Understanding of Multiple Documents - Mahlow, Nina; Hahnel, Carolin; Kroehne, Ulf; Artelt, Cordula; Goldhammer, Frank; Schoor, Cornelia (Frontiers in Psychology, 2020)
The digital revolution has made a multitude of text documents from highly diverse perspectives on almost any topic easily available. Accordingly, the ability to integrate and evaluate information from different sources, known as multiple document comprehension, has become increasingly important. Because multiple document comprehension requires the integration of content and source information across texts, it is assumed to exceed the demands of single text comprehension due to the inclusion of two additional mental representations: the integrated situation model and the intertext model. To date, there is little empirical evidence on commonalities and differences between single text and multiple document comprehension. Although the relationships between single text and multiple document comprehension can be well distinguished conceptually, there are a lack of empirical studies supporting these assumptions. Therefore, we investigated the dimensional structure of single text and multiple document comprehension with similar test setups and examined commonalities and differences between the two forms of text comprehension in terms of their relations to final school exam grades, level of university studies and university performance. Using a sample of n=501 students from two German universities, we jointly modelled single text and multiple document comprehension and applied a series of regression models. Concerning the relationship between single text and multiple document comprehension, confirmatory dimensionality analyses revealed the best fit for a model with two separate factors (latent correlation: .84) compared to a two-dimensional model with cross-loadings and fixed covariance between the latent factors and a model with a general factor. Accordingly, the results indicate that single text and multiple document comprehension are separable yet correlated constructs. Furthermore, we found that final school exam grades, level of university studies and prior university performance statistically significant predicted both single text and multiple document comprehension and that future university performance was predicted by multiple document comprehension. There were also statistically significant relationships between multiple document comprehension and these variables when single text comprehension was taken into account. The results imply that multiple document comprehension is a construct that is closely related to single text comprehension yet empirically differs from it.